2003
DOI: 10.1152/ajprenal.00308.2002
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to genetic manipulation of mice: tissue-specific expression of ACE

Abstract: . New approaches to genetic manipulation of mice: tissue-specific expression of ACE. Am J Physiol Renal Physiol 284: F599-F607, 2003; 10.1152/ajprenal.00308. 2002The renin-angiotensin system (RAS) plays a central role in body physiology, controlling blood pressure and blood electrolyte composition. ACE.1 (null) mice are null for all expression of angiotensin-converting enzyme (ACE). These mice have low blood pressure, the inability to concentrate urine, and a maldevelopment of the kidney. In contrast, ACE.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…Controls included identically prepared cells from wild-type mice and a previously reported line of mice called ACE 4/4 that is null for ACE expression, except for male germ cells. 16 Because the two control populations gave identical results, we only show data from wild-type mice. When cells were gated and compared for the level of ACE expression, no ACE expression was detected in the T or B cells of either ACE 10/10 or control mice.…”
Section: Resultsmentioning
confidence: 99%
“…Controls included identically prepared cells from wild-type mice and a previously reported line of mice called ACE 4/4 that is null for ACE expression, except for male germ cells. 16 Because the two control populations gave identical results, we only show data from wild-type mice. When cells were gated and compared for the level of ACE expression, no ACE expression was detected in the T or B cells of either ACE 10/10 or control mice.…”
Section: Resultsmentioning
confidence: 99%
“…81 Evidence supports that local Ang II synthesis occurs in select tissues. [82][83][84][85] Tissues expressing all or most of the components of a local RAS include the heart, smooth muscle vasculature cells, kidney, brain, adrenal gland, pancreas, placenta, testes and adipose tissue. Overexpressing RAS genes in animals and RAS knockout models have allowed investigators to detail the presence and function of a local RAS in a variety of tissues.…”
Section: Effects Of Local Renin-angiotensin System I Presence Of Locmentioning
confidence: 99%
“…These studies showed no difference in response in the magnitude, time response, or shape of the pressure curves between wild-type and either ACE 7/7 or ACE 1/7 mice. As a control, we used a strain of ACE knock-out mice called ACE 4/4 (26). These mice are similar to ACE null mice (ACE 1/1) except that they retain normal expression of testis ACE.…”
Section: Generation Of Genetically Modifiedmentioning
confidence: 99%